Manajemen Utang Dalam Perspektif Islam : Terhadap Produk Pembiayaan Berbasis Syariah (Murabahah Dan Qardhul Hasan): Studi Literatur pada peran Akad dalam Lembaga Keuangan Syariah - Nurul Firdausah; Rini Puji Astuti; Nia Safira Aprilia Firdaus (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This research was conducted to answer the problem of the role of murabahah and qardhul hasan contracts as alternative debt for the community. The type of research used is descriptive qualitative. By using secondary data derived from the theories of various literatures and data that emerged from an institution. . The results of this study show that these two contracts have a complementary role in providing financing solutions that comply with sharia principles and meet the needs of people from various economic segments. Murabahah reaches productive customers who need financing with a structured plan, while qardhul hasan reaches vulnerable people who need financial assistance without the pressure of interest.